Eventos adversos em terapia medicamentosa em Unidade de Terapia Intensiva - UTI - Coelho, Monique Antonia [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Due to the complexity and instability of clinical conditions of ICU patients, the drug therapy applied in this type of environment requires a combination of several prescribed drugs, which is a favorable condition for drug interaction, toxic synergism and possible iatrogenia. In the possible universe of ICU occurrences, this study aimed at identifying and evaluating the incidence of adverse events in drug therapy at the Intensive Care Therapy Service (SETI) in wards I and II. It is a cross-sectional, descriptive, prospective and quantitative study conducted from August to September, 2011 in the Intensive Care Service of the Botucatu School of Medicine University Hospital - UNESP. The population consisted of fifteen clinical nurses, including those in the Improvement and Volunteer Internship Programs, who contributed to the investigation after signing an informed consent form and according to approval by the Research Ethics Committee number 10711/CE - FMB. The data were entered on a form and analyzed. Results showed that, on average, 8.9% of events/day occurred, and the highest frequency was observed on August 04, 2011. 63% and 22% were respectively observed in the morning and afternoon shifts, and 15% in the night shift. 48% of these were due to administration time errors, followed by drug prescription and dispensation errors, with percentages of 22% and 18%, respectively. Antibiotics showed the highest frequency of adverse events - 18%, which was followed by 13% for anticoagulant, 11% for antiemetic and 10% for antiulcerative drugs. As regards the occurrence of adverse events related to hospitalization time, the highest frequency occurred in patients who were hospitalized for 10 days. Concerning the ratio between reported events and the number of items in the prescription, the highest frequency of events was related to prescriptions with 20 items... (Complete abstract click electronic access below)

Em decorrência da complexidade e instabilidade do quadro clínico dos pacientes em UTI, a farmacoterapia aplicada nesse tipo de ambiente exige uma combinação de diversas drogas prescritas, sendo assim uma condição favorável para interações medicamentosas, sinergismos tóxicos e possíveis iatrogenias. Dentre o universo possível de ocorrências na UTI, este estudo tem como objetivo identificar e avaliar a incidência de eventos adversos em terapia medicamentosa no Serviço de Terapia Intensiva – SETI nas alas I e II. Trata-se de um estudo transversal, descritivo, prospectivo de abordagem quantitativa desenvolvido no período de Agosto a Setembro de 2011 no Serviço de Terapia Intensiva do Hospital das Clínicas da Faculdade de Medicina de Botucatu da Universidade Estadual Paulista Júlio de Mesquita Filho - UNESP. A população foi composta por quinze enfermeiros assistenciais, incluindo a enfermeira do aprimoramento e do estágio voluntário prático que colaboraram com a investigação após assinatura do Termo de Consentimento Livre e Esclarecido conforme o parecer favorável do Comitê de Ética número10711/CE FMB. Os dados foram preenchidos em um formulário, analisados e com os resultados constatou-se que: em média ocorreram 8,9% de eventos/dia, sendo observada a maior frequência no dia 04/08/2011. 63% e 22% foram identificados respectivamente nos turnos da manhã e tarde e, 15% no plantão noturno. 48% deles se devem ao erro de horário, seguido de erro na prescrição e dispensação dos medicamentos, com uma porcentagem de 22% e 18%, respectivamente. Com a maior frequência de 18% de eventos adversos tem-se a classe dos Antibióticos, seguida de 13% Anticoagulantes, 11% Antieméticos e 10% Antiulcerosos. Quanto à ocorrência de eventos adversos relacionados ao tempo de internação hospitalar, a maior frequência deu-se em pacientes que permaneceram internados por 10 dias... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Doenças iatrogenicas; Erros de medicação; Unidade de tratamento intensivo